Strategi Pengembangan SDM Maritim Indonesia Berbasis Kearifan Lokal - Muhammad Nawir; Jusfira Yuniar; Dahniar Nur; Agung Indra Wijaya (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
With thousands of islands and long beaches, Indonesia is the largest archipelagic country in the world. With this geographical diversity, there is a lot of potential in the maritime sector, including abundant marine resources. Indonesia's maritime affairs greatly influence its history, culture and economic progress. There is no doubt that Indonesia's rich maritime resources must be utilized properly so that they can become a sustainable resource for the country's future. The method used is library research. Specific characteristics that are used as a basis for developing research knowledge include; This research is confronted directly with the data or text presented, not with field data or through eyewitnesses in the form of events, researchers only deal directly with sources that already exist in the library or ready-to-use data, as well as secondary data used. The results obtained are: To ensure the sustainability of its rich and important maritime sector, Indonesia can utilize its rich maritime traditions as capital to achieve sustainable economic growth and preserve the marine environment. Indonesia has the opportunity to build a generation that is aware of the importance of maintaining the sustainability of marine ecosystems and local wisdom as an important cultural heritage.